ANALISIS RISIKO RANTAI PASOK KOMODITAS CENGKEH DI KECAMATAN SALANG KABUPATEN SIMEULUE - Heri Tri Irawan; Iing Pamungkas; Muzakir Muzakir (Universitas Teuku Umar, 2019)
The concept of supply chain management is a new concept that sees all company activities as an integrated part. In this case the integration of the company in the upstream (upstream) in providing raw materials and integration in the downstream (downstream) in the process of product distribution and marketing. This study aims to analyze the supply chain system of clove commodities in Simeulue Regency which is more effective and efficient so that it can be applied by the community, especially clove farmers. The method used in this research is to use the HOR (House of Risk) method. From the house of risk mapping results, 6 selected risk agents will be used as consideration material in the preparation of mitigation actions, namely: A-7 (Inadequate transportation technique) with an ARP value of 330, A-3 (Lack of experience in finding supply of raw materials) with an ARP value of 288, A-13 (Non-compliance with clove shipping documents) with an ARP value of 276, A-9 (Ineffective communication) with an ARP value of 258, A-11 (Non-compliance with the agreement with the supplier of cloves) by default ARP 189 and A-15 (Failure of price negotiations with producers) with an ARP value of 126.